2021
DOI: 10.48550/arxiv.2102.01706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

APOGEE discovery of a chemically atypical star disrupted from NGC 6723 and captured by the Milky Way bulge

José G. Fernández-Trincado,
Timothy C. Beers,
Dante Minniti
et al.

Abstract: The central ('bulge') region of the Milky Way is teeming with a significant fraction of mildly metal-deficient stars with atmospheres that are strongly enriched in cyanogen ( 12 C 14 N). Some of these objects, which are also known as nitrogen-enhanced stars, are hypothesised to be relics of the ancient assembly history of the Milky Way. Although the chemical similarity of nitrogen-enhanced stars to the unique chemical patterns observed in globular clusters has been observed, a direct connection between field s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Following the same methodology as described in Fernández-Trincado et al (2021a), we compute the predicted number (N N−rich ) of N-rich field stars observed in APOGEE-2 toward M 54/Sgr using the smooth halo density relations presented in Horta et al (2021), and by adopting the same Monte Carlo implementation of the Von Neumann Rejection Technique (see e.g., Press et al 2002) as in Eq. 7 in (Fernández-Trincado et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Following the same methodology as described in Fernández-Trincado et al (2021a), we compute the predicted number (N N−rich ) of N-rich field stars observed in APOGEE-2 toward M 54/Sgr using the smooth halo density relations presented in Horta et al (2021), and by adopting the same Monte Carlo implementation of the Von Neumann Rejection Technique (see e.g., Press et al 2002) as in Eq. 7 in (Fernández-Trincado et al 2015).…”
Section: Resultsmentioning
confidence: 99%